2014
DOI: 10.1021/ol503000c
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Aminooxygenation and Diamination of Alkenes with Amidines by Hypervalent Iodine(III) Reagents

Abstract: Diastereoselective anti-aminooxygenation and anti-diamination of alkenes with amidines were enabled by hypervalent iodine(III) reagents such as PhI(OCOR)2 and PhI(NMs2)2, respectively. The present transformation offers diastereochemically pure dihydroimidazoles divergently from E- and Z-alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 85 publications
0
26
0
Order By: Relevance
“…In the same year, Chen et al reported a hypervalent iodine-mediated diastereoselective anti-aminooxygenation and anti-diamination of alkenes with amidines to synthesize 2-imidazolines (Scheme 73). [74] Initial in- vestigations to obtain suitable conditions were performed by using a few hypervalent iodine(III) reagents (PhI(OCOCH 3 ) 2 , PhI(OCOCF 3 ) 2 , PhI(OCOPh) 2 ) with the amidine (R 1 , R 2 , R 3 = Ph; R 4 , R 5 = H) (258) in different solvents. Both bis-acetate and bis-trifluoroacetate containing iodine reagents worked efficiently in dichloromethane.…”
Section: Methods C: Synthesis Of Imidazolines From Amidinesmentioning
confidence: 99%
“…In the same year, Chen et al reported a hypervalent iodine-mediated diastereoselective anti-aminooxygenation and anti-diamination of alkenes with amidines to synthesize 2-imidazolines (Scheme 73). [74] Initial in- vestigations to obtain suitable conditions were performed by using a few hypervalent iodine(III) reagents (PhI(OCOCH 3 ) 2 , PhI(OCOCF 3 ) 2 , PhI(OCOPh) 2 ) with the amidine (R 1 , R 2 , R 3 = Ph; R 4 , R 5 = H) (258) in different solvents. Both bis-acetate and bis-trifluoroacetate containing iodine reagents worked efficiently in dichloromethane.…”
Section: Methods C: Synthesis Of Imidazolines From Amidinesmentioning
confidence: 99%
“…Analogously, in 2014, Chiba and coworkers reported an efficient hypervalent iodine enabled diastereoselective anti-aminooxygenation and anti-diamination of N-allylamidines 20 for the synthesis of dihydroimidazoles 21 [22]. Zhu and coworkers [23] developed a metal-free intramolecular C-H amination reaction of N-aryl-2-aminopyridines 22 catalyzed by a hypervalent iodine(III) species generated in situ from iodobenzene and peracetic acid for the synthesis of pyrido[1,2-a]benzimidazoles 23 (Scheme 5).…”
Section: Annulation Through Electrophilic Nitrogenmentioning
confidence: 98%
“…Chiba group developed PIDA ( 1 ) mediated method for diastereoselective anti ‐aminooxygenation of alkenes with amidines 194 to produce dihydroimidazoles 195 divergently from E ‐ and Z ‐alkenes (Scheme a) . The hypervalent iodine(III) reagent PIFA ( 2 ) was used to accelerate the reaction with amidine 194 , leading to full conversion anti ‐aminohydroxylation product 196 in 82 % yield.…”
Section: Intramolecular Oxidative C(sp2)‐n Bond Formationmentioning
confidence: 99%